Analisis Perkembangan Pinjaman Online Di Era Revolusi Industri 4.O Pada Mahasiswa Gen Z Universitas Nusa Cendana Kupang - Yerisonsianus Peron; Fransina W. Ballo; Novi Theresia Kiak (Universitas Kristen Indonesia Toraja, 2024)
This research aims to analyze the influence of Lifestyle, Needs and Access to Financial Institutions on Online Loans among GEN-Z students at Nusa Cendana University, Kupang. This research uses quantitative methods with a quantitative descriptive approach. Determining the sample in this study used a purposive sampling method. The number of samples in this study was 100 samples and was determined based on the Slovin formula. The data collection technique used a questionnaire distributed to all students at Nusa Cendana University, Kupang. Data analysis used in this research is data quality test (validity test and reliability test), classic assumption test (normality test, multicollinearity test, heteroscedasticity test), multiple linear regression analysis, hypothesis test (t test and f test) and determination test (R2). The results of the research state that variable X1 has no effect on variable Y, variable X2 has an effect on variable Y and variable X3 has an effect on variable Y. Variables X1,